Penerapan Metode Solfegio sebagai Strategi Pembelajaran Vokal pada Kegiatan Ekstrakurikuler Musik di SMK TI NWDI Wanasaba - Julina Susanti; Alwan Hafiz; M. Alfian Nur Khair (Mataram University, 2026)
This study describes the application of the solfège method as a vocal learning strategy in the music extracurricular program at SMK TI NWDI Wanasaba and its impact on students' vocal ability. Vocal training in the program still relied on habit and imitation, so students rarely received systematic music theory. This condition motivated the study. The problems behind the research were unstructured vocal learning, the coach's limited mastery of vocal technique, and students' weak understanding of intonation and rhythm. The study used a qualitative descriptive approach. The researcher collected data through observation, interviews, and documentation involving the coach and four extracurricular students, then tested the data through source triangulation and analyzed it with the Miles and Huberman model. The results show that the solfège method was applied in stages through warm-up, notation introduction, ear training, sight singing, song practice, and evaluation. This process turned training that once relied on habit into a structured and concept-based process. The solfège method gave a positive impact on seven vocal aspects, namely understanding of the solfège concept, vocal technique, diaphragmatic breathing, intonation, solmization, body posture and articulation, and interpretation and expression, and it also grew students' confidence. The study concludes that the solfège method is suitable as a vocal learning strategy in music extracurricular programs at the vocational high school level.